Prioritising Scientific Data In Covid-19 Vaccine Policy - Ahmad Mahfuz, Gazali (Social Health Analytics Sdn Bhd, 2022)
Public health policy mandating Covid-19 booster shots in those who received Sinovac vaccine and the elderly is supported by considerable evidence from scientific data.